DESIGNING E-CHARACTER ONLINE: AN EXAMINING ON INDONESIAN UNDERGRADUATE STUDENTS - Nani Barorah Nasution; Nasrun Nasrun; Erwita Ika Violina (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2022)
Character education is one of the missions in Universities as a place for ordering prospective educators. In this research, we focused on develop designing an online web for developing character values: Discipline, Justice, Respect, Responsibility, Care and Citizenship. This is a Research and Development (R&D) study that aims to determine the development and feasibility of the Character Education Program with Web-based Application media at the Universitas Negeri Medan. Development models are 4-D models (Define), (Design), (Develop) and (Disseminate). The number of samples was 100 students of guidance and counseling undergraduate students that were randomly selected